Determination of Parameters for Assessing Bus Transit and Service Area Relationships along EDSA. - Icasiano, Daniel Angelo A.; Antonio, Catherine Anne D.; Regidor, Jose Regin F.
Through the use of boarding and alighting data from a thoroughfare spanning across a metropolis, it can be possible to derive associations between transit activity and area characteristics. This study aims to determine statistical relationships between bus transit use and service area characteristics along the main artery of Metropolitan Manila. GIS and multi-linear regression analysis are used to establish the relationships. Evaluation and validations of the runs were executed in order to select the parameters. Numerical descriptions of the influences are developed. These establish certain land parameters to be useful for an effective modeling of the transit activity along the thoroughfare.
Keywords: Bus transit; Parameters; Land use; Population; Service area